Sistem informasi geografis dalam pemetaan angka kematian ibu di Kabupaten Kebumen - Ivan Tinarbudi Gavinov; Mutiara Nabilah (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Maternal mortality rate (MMR) has become an important indicator of public health status. MMR describes the number of women who died from a cause of death related to a pregnancy disorder or their treatment (excluding accidents or incidental cases) during pregnancy, childbirth and in the puerperium (42 days after delivery) without taking into account the length of pregnancy per 100,000 live births. Maternal Mortality Cases in Kebumen District from 2012-2016 can be seen that there has been an increase in the last two years ie 2015 and 2016. The latest data of 2016 was recorded at 80.01 Per 100,000 Birth of Life (KH). As for the target RPJMD is 49 per 100,000 KH which means the number of achievements Kebumen still far from the expected target. Analysis of the distribution of existing cases is already in the form of mapping but only at the point of the kecamatan. This type of research used quantitative descriptive research with the design of a case-control study. The sample for this study is 32 respondents were 16 case respondents and 16 respondents control. Data analysis method with spatial analysis, univariate and bivariate analyzes with logistic regretion test with 95% confidence level. Univariate Analysis were 16 case respondents and 16 respondents control. Based on bivariate analysis indicated that independent variables were have relationship with dependent variable that is the distance of house to puskesmas (p = 0,000) and travel time to puskesmas (p = 0,000). Another factor that influences is the existing road conditions in Kebumen. After the research on respondents, it can be concluded that there is a significant relationship between the distance and travel time with the incidence of maternal mortality in Kebumen.